2014
DOI: 10.1080/13527266.2013.841273
|View full text |Cite
|
Sign up to set email alerts
|

A cross-national study of Twitter users’ motivations and continuance intentions

Abstract: Given the explosive popularity and growth of microblogging worldwide and its potential use in the areas of public policy, civic activism, as well as marketing and advertising, the questions of why and how individuals use these services warrant a comprehensive research. While some studies addressing motivations to join and continue using Twitter have been published, no research to date has investigated these issues in the context of developing economies. This exploratory study seeks to build an understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 21 publications
(24 reference statements)
3
25
0
1
Order By: Relevance
“…Further, the constructs, status seeking and information seeking have a direct influence on continuance intention. These findings were supported by the studies of Li et al (2015), Mäntymäki and Riemer (2014) and Wohn and Lee (2013) with Pentina et al (2014) indicating that 34.6% of the variance in sharing experience is explained by status seeking and information seeking.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 76%
See 3 more Smart Citations
“…Further, the constructs, status seeking and information seeking have a direct influence on continuance intention. These findings were supported by the studies of Li et al (2015), Mäntymäki and Riemer (2014) and Wohn and Lee (2013) with Pentina et al (2014) indicating that 34.6% of the variance in sharing experience is explained by status seeking and information seeking.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 76%
“…These results were expected based on the findings of Baek et al (2014), Ko et al (2005), Luo et al (2011), Malik et al (2016, Pentina et al (2014). They demonstrated that the success of Second Life in the e-learning processes depends on a combination of convenience, sharing experience and the search for more entertaining educational programmes.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 52%
See 2 more Smart Citations
“…Jahn and Kunz, 2012;Muntinga et al, 2011;Pentina et al, 2016;Pletikosa Cvijikj and Michahelles, 2013;Rohm et al, 2013;Whiting and Williams, 2013;Zolkepli and Kamarulzaman, 2015). Within the sport context, U&G theory has been predominantly used in user-focused studies (Abeza et al, 2015;Filo et al, 2015).…”
Section: Uses and Gratifications Theorymentioning
confidence: 99%